2020
DOI: 10.1177/0734242x19897123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrothermal pre-treatment on physical properties and co-digestion from food waste and sewage sludge mixture

Abstract: Anaerobic digestion (AD) is generally considered to be an economic and environmentally friendly technology for treating waste activated sludge, but has some limitations, such as the time it takes for the sludge to be digested and also the ineffectiveness of degrading the solids. Various pre-treatment technologies have been suggested to overcome these limitations and to improve the biogas production rate by enhancing the hydrolysis of organic matter. This paper studies the use of hydrothermal pre-treatment (HTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The AD batch worked for forty days in mesophilic temperature (38 °C). The assessment results that an HTP of 140°C enhances the production of biogas by 50% (Park et al, 2020) and in this research, all cases were studied under mesophilic conditions (35-37 °C) for 23 days according to Table 4 and found that R2(140) is the optimal reactor and the improvement in biogas production reaches about 29.65%. Moreover, at 160 and 180 °C, although high removal of COD occurred, the biogas production was still higher in the reactor R2(140).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The AD batch worked for forty days in mesophilic temperature (38 °C). The assessment results that an HTP of 140°C enhances the production of biogas by 50% (Park et al, 2020) and in this research, all cases were studied under mesophilic conditions (35-37 °C) for 23 days according to Table 4 and found that R2(140) is the optimal reactor and the improvement in biogas production reaches about 29.65%. Moreover, at 160 and 180 °C, although high removal of COD occurred, the biogas production was still higher in the reactor R2(140).…”
Section: Resultsmentioning
confidence: 69%
“…There was no decrease in the pH values. This is most likely due to the reactions that occurred between ammonia and carbon dioxide, which produce bicarbonate (Park et al, 2020). The final pH values at the end of the co-digestion process were 7.23 and 7.72.…”
Section: Resultsmentioning
confidence: 99%
“…A standard procedure (APHA) was used to characterize the fruit waste sample (Park et al, 2020). Protein was measured using Lowry's method and carbohydrate was determined using the anthrone sulphuric acid method (Arun and Sivashanmugam, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…From the calculation, the ultimate methane yield for FW and FW50 was 1033.6 mLCH4/gVS and 1657.8 mLCH4/gVS, respectively. Previous researchers found the ultimate methane yield for FW and FW50 falls in the range of 200 -900 mLCH4/gVS and 350-1200 mLCH4/gVS, respectively [13,16,34,37]. However, Seswoya et al [26] showed that the ultimate methane yield for FW was exceeded 1000 CH4/gVS.…”
Section: Ultimate Methane Yieldmentioning
confidence: 96%